(3SjQI QShd Gddg Udi Gddg Ydjg hSdes - (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s ((3eMeO Hf CMeO Hf CMeO GdbOSi s)
(3ChdgG (B:s
(3Ghdg CeQ CHj bjS Hf C Hi CfS s
(3BNQgG (B:s
(3hjfJgi BNQg HCNHGQ Hfi bQjXI s
(3fSNI MGOjI YTQIs
(3hGdehLhO efgG GdLRA GdKGfis
(3hHBNQgG bQGAI eDQNI SfI (B866(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs